2010
DOI: 10.1100/tsw.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

Stress Proteins and Pancreatic Cancer Metastasis

Abstract: Tumor metastasis is challenged by its resistance to microenvironmental stress infringed during escape from the primary tumor and the colonization of a foreign secondary tissue. Because of its great metastatic potential and its strong resistance to anticancer drugs, pancreatic cancer is regarded as a paradigm of the adaptation of cancer cells to microenvironmental stress. Thus, to understand how pancreatic cancer cells adapt to the different endogenous and therapy-related stresses is crucial for understanding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…15 In this case, the nanoparticles could be acting on the Nupri1 gene, which encodes p8 protein in order to prevent cell death. 16 Therefore, the presented results demonstrate that Ce NP pretreatment prevented cell death and increased cell viability upon starvation stress. This indicates that nano-CeO 2 might stimulate cell survivor mechanisms, such as higher expression of p8 and Bcl-2 proteins.…”
Section: Discussionmentioning
confidence: 54%
“…15 In this case, the nanoparticles could be acting on the Nupri1 gene, which encodes p8 protein in order to prevent cell death. 16 Therefore, the presented results demonstrate that Ce NP pretreatment prevented cell death and increased cell viability upon starvation stress. This indicates that nano-CeO 2 might stimulate cell survivor mechanisms, such as higher expression of p8 and Bcl-2 proteins.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that NUPR1 is involved in chemoresistance in breast and pancreatic cancers. 38, 39 Here we demonstrated that NUPR1 depletion led to a significant increase in HCC cell sensitivity to sorafenib treatment, suggesting that it may also have a pivotal role in HCC chemoresistance.…”
Section: Discussionmentioning
confidence: 66%
“…For instance, we reported Nupr1 antiapoptotic function against the anticancer drug gemcitabine (23), which is at present the first choice for PDAC treatment. Nupr1 regulates in part the cell response to stress through the modulation of target gene expression (24). In addition, Nupr1 regulates chromatin accessibility through its interaction with proteins implicated in histone acetylation/deacetylation and may thereby modulate the genetic response to stress (25).…”
Section: Introductionmentioning
confidence: 99%